CDCDB: A large and continuously updated drug combination database - Guy Shtar; Louise Azulay; Omer Nizri; Lior Rokach; Bracha Shapira (Scientific Data, 2022)
Measurement(s) drug combination effect modeling • drug combination effect modeling Technology Type(s) Text mining • Clinical Trials Informatics System Factor Type(s) Medicine Sample Characteristic - Organism Homo sapiens